Synthesis and Characterization of A New Cadmium Complex, Cadmium [(1, 10-phenanthroline)(8-hydroxyquinoline)]Cd(Phen)q. (2015) - Kumar, Rahul; Bhargava, Parag; Dvivedi, Avanish
Abstract: A new photoluminescence material cadmium [(1, 10-phenanthroline)(8-hydroxyquinoline)] Cd(Phen)q has been synthesized and characterized. The prepared material Cd(Phen)q was characterized by Fourier-infrared spectroscopy(FTIR), Nuclear magnetic resonance spectroscopy (NMR), Thermo gravimetric analysis (TGA), UV-visible spectroscopy and photoluminescence (PL). Solution of this material Cd(Phen)q in toluene showed absorption maxima at 256 nm and 295 nm which may be attributed to the moderate energy ( π – π*) transitions of the aromatic rings while absorption maxima at 335 nm and 387 nm observed were due to the coordination of cadmium and organic ligands (Phen and q). The photoluminescence spectrum of Cd(Phen)q in toluene solution showed peak at 510 nm. This material is thermally stable up to 400 0 C. The time resolved photoluminescence spectra of this material Cd(Phen)q showed two life time components, 3.8 ns and 15 ns respectively.